2003
DOI: 10.1177/004947550303300419
|View full text |Cite
|
Sign up to set email alerts
|

Vernal Keratoconjunctivitis in Nigerians: 109 Consecutive Cases

Abstract: Vernal keratoconjunctivitis was the most common conjunctival disease seen over a 2 year period (January 1997-December 1998) at the University of Benin Teaching Hospital, Benin City, Nigeria. One hundred and nine consecutive patients were seen with vernal keratoconjunctivitis. There was a male to female ratio of 1:1.3. The age range of the patients was 5 months to 38 years with a mean age of 15.5 +/- 8.3 years (SD). Of the patients 54.1% were children. Itching was the most common symptom, followed by redness, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 7 publications
6
46
1
2
Order By: Relevance
“…However, other African studies have found no gender difference. 5,8,17 Studies from Europe 9 and Africa 45 have also found that girls are at significantly greater risk of developing VKC in their second decade. This may result from the increased production of androstenedione around puberty in girls.…”
Section: Discussionmentioning
confidence: 99%
“…However, other African studies have found no gender difference. 5,8,17 Studies from Europe 9 and Africa 45 have also found that girls are at significantly greater risk of developing VKC in their second decade. This may result from the increased production of androstenedione around puberty in girls.…”
Section: Discussionmentioning
confidence: 99%
“…9 The multi centric study from Italy reported IJBR (2014) 05 (04) www.ssjournals.com predominance of limbal form about 53.8%, 10 whereas Ukponmwan reported 82.6% cases with palpebral presentation in Nigeria. 11 This signifies that the prevalence of subtypes of VKC is different in various parts of the world. VKC can cause various corneal complications leading to decreased vision.…”
Section: Discussionmentioning
confidence: 99%
“…Em um estudo de cohort de 62 pacientes na Suécia, a freqüên-cia de alergia extra-ocular em pacientes com CCP variou de acordo com o grupo étnico de 8,3% em asiáticos a 100% em latino-americanos. Em 109 pacientes consecutivos avaliados em um período de dois anos na Nigéria, apenas 4,5% apresentavam alergia extra-ocular (21) . No Brasil, estudos encontraram 76% de positividade de teste cutâneo para hipersensibilidade imediata (Prick test) em pacientes com CCP (22) .…”
Section: Discussionunclassified